(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate level of stress, anxiety and depression among Final year MBBS students of King Edward Medical University, Lahore and its impact on their academic performance. Study Desin: Cross Sectional study. Place and Duration of Study: This study was conducted at the Department of Anatomy, King Edward Medical University, Lahore from 11th January, 2017 to 12th March, 2017. Materials and Methods: A total of 100 questionnaire were distributed randomly among final year MBBS students of King Edward Medical University, Lahore who were enrolled in MBBS program during that time of study. Consent forms were filled by all students. Questionnaire comprised of demographic variables, DASS (Depression, Anxiety and Stress Score) 21 Score and last professional examination marks in percentages. Mean scores were calculated. Relationship of DASS 21 scores with different categories of students and gender were also calculated. Results: A total of 81 final year MBBS students filled the form. Among those, 70.4% were females and 29.6% were males. The DASS Stress score calculated to be 9.2 ± 4.7. DASS Anxiety Score calculated to be 7.19 ± 4.54. DASS Depressions score calculated to be 8.96 ± 4.1. Majority of the high achievers were having high anxiety and stress score. As compared to males, females were having high stress and depression scores. Conclusion: High achievers and females are experiencing more depression and anxiety as compared to low achievers and males, respectively.